Färre och färre händer - Gyllemark, Caroline (2008)
This degree project is based on my personal relation and engagement to the small-scaled cultural landscape. My viewpoint is the village Torpa in Östergötland. My observations of the changes and development together with the stories of the village people has lead me to the questioning about the future prospects of the small-scaled cultural landscape. The rationalization of the society and our urban culture has lead to big changes in the cultural landscape and the people have reduced to a small crowd. Fewer and fewer hands are managing the small-scaled cultural landscape and fewer and fewer young people have connection to this kind of landscape and its management. The cultural landscape is reducing and grows over, the agricultural companies get bigger, fewer and more specialized and soon there will be many pension retirements in the agricultural sector. Many of today's Swedish farms have no heir or heiress. Sweden operates its environmental issues on the basis of sixteen environmental goals and one of those is Ett rikt odlingslandskap. The small-scaled cultural landscape has many great values and its future existence is completely dependent on the younger generation taking over and managing the landscape. The question is if enough of today's youth, who has more choices and opportunities than yesterday's youth, will choose to go on managing the small-scaled cultural landscape? By searching for contextual knowledge and meet and talk with the people out in the field I have tried to get clarity in my own questioning about the future prospects of the small-scaled cultural landscape and tomorrow's landscape managers.